Investigating Vaccination Failure in Poultry Flocks - Gary D. Butcher; Mojtaba Yegani (EDIS)
VM-174, a 5-page fact sheet by Gary D. Butcher and Mojtaba Yegani, discusses disease management in poultry, why vaccination is used and reasons why a vaccine may fail to protect the flock. Includes references. Published by the UF College of Veterinary Medicine Department of Large Animal Clinical Sciences, November 2008.